An Analysis of the Impact of Famers’ Practices on Pesticide Residue Levels in Chili Pepper Commodities in West Java - Rusydan, Muhammad Ardillah; Dono, Danar; Sudarjat, Sudarjat (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2025)
Chili plants are highly susceptible to infestations by various Plant Pest Organisms (OPT) such as fruit flies, thrips, leaf-eating caterpillars, and fruit borers, as well as diseases like anthracnose, root rot, and leaf spot. To manage these threats, most farmers still rely on synthetic chemical pesticides. Improper pesticide application—particularly in terms of dosage and frequency—can lead to pesticide residues on harvested crops and pose risks to both the environment and human health. This study aims to analyze farmers' behavior in pesticide use and to measure pesticide residue levels in chili samples collected from three major production centers in West Java: Arjasari, Lembang, and Garut. A mixed-method approach combining qualitative interviews and quantitative High-Performance Liquid Chromatography (HPLC) analysis was used to evaluate six active pesticide ingredients. The results showed that most farmers applied pesticides beyond the recommended dosage and frequency. Residues of chlorothalonil and broflanilide were detected in the samples, with concentrations exceeding the Maximum Residue Limits (MRLs). These findings highlight the urgent need for education and stricter oversight regarding pesticide application practices among farmers.